Implementasi Program Gema Tasamara (Gerakan Masyarakat Tangkasa Na Gammara) Di Kabupaten Takalar - Masiga, Hasriani; Malik, Ihyani; Andriana, Andriana (Universitas Muhammadiyah Makassar, 2022)
This study aimed to find out the implementation of the Gema Tasamara Program (Tangkasa na Gammara Community Movement) in Takalar Regency. The research method used descriptive qualitative and the instruments used observation, interviews and documentation. The number of informants in this study were 10 people. Data analysis included data reduction, data presentation and conclusion making. The results of the study showed that the implementation of the GEMA TASAMARA program in Takalar Regency in general had not been maximized in terms of major indicators, namely the content of the policy included the interests of the target group, the benefits of the program felt by the community, the degree of change to be achieved, the location of the decision makers, namely the local government was not serious. In dealing with problems related to environmental management and protection, in this case environmental hygiene, there were still piles of garbage in some areas in Takalar Regency, the program implementers were quite good, namely the Department of Environment and Land in Takalar Regency, but the resources were not adequate, then environmental indicators for implementation included the power, interests and strategies of actors who lacked socialization, characteristics of institutions and regimes that lacked communication with the community and the level of compliance of the implementers was quite good.Keywords: Implementation, Program, Gema Tasamara